Estimating and communicating the risk of neglecting maintenance. Issue 2 (30th November 2018) - Adey, Bryan T; Martani, Claudio; Papathanasiou, Natalia; Burkhalter, Marcel
Abstract : The difficulties of engineers and managers agreeing on how to invest in infrastructure maintenance stem from a basic inability to communicate with each other. This leads to the suboptimal management of infrastructure. Luckily, this situation can be remedied by engineers learning how to communicate their concerns in a way that managers can understand, so that they can clearly see whether a proposed action needs to be taken or can be deferred. This paper shows, with the help of a realistic example, in terms of infrastructure, methodology and techniques, how this can be done. The proposed approach, although upon reading is perhaps intuitive, is starkly absent in the literature in the field of infrastructure asset management. In the proposed approach, it is demonstrated how to improve the traditional approaches used by engineers to communicate to managers through ( a ) the quantification of the level of service as seen by mangers, ( b ) the modelling of how infrastructure might not provide the required level of service and ( c ) the way of showing how intervention programmes can affect the provision of service, both now and in the future.